The impact of economic slowdown on residential property market - effectiveness of government financial measures / Hamyzar Toha - Toha, Hamyzar (2000)
September 1997 will always be remembered by all the Malaysian people as the date where never before the country having such a stiff and crucial test against its economic structure. After almost a decade of economic prosperity, Malaysia, which was also known as one of the Asian economic tiger, was thrown into an economic debacle as currency and financial turmoil battered the whole region. Caught by surprise, the Government at that time, following an advice from International Monetary Fund (IMF) had introduced several fiscal and financial measure to cater for the situation arise, but unfortunately, the measure taken proved to be disastrous and bring the economic almost to a halt. Realising the effect of the measures taken, the Government embarked on new strategies of economic reformation to deal with the crisis and to prevent a more damaging impact to the country's economic system.